1дм-1см=

3дм7см+3см=

5дм9см-4дм=

6дм7см-6см= Написать выражения помощники

2

Ответы и объяснения

2014-02-25T18:54:07+04:00
10см-1см=9 см
37см+3см=40см
59см-40см=19см
67см-6см=61см
2014-02-25T18:58:09+04:00
1дм-1см;1дм=10см;10см-1см=9см                                                                                     3дм7см+3см;37см+3см=40см=4дм                                                                           5дм9см-4дм;49см-40см=9см                                                                                               6дм7см-6см;67см-6см=61см